Vers une transition des systèmes agricoles en France métropolitaine ? Une géographie contrastée et en mouvement (2010 et 2020) - Michaël Bermond; Pierre Guillemin (Cybergeo)
In light of the decarbonization objectives in agriculture, environmental preservation, and the resulting challenges of economic sustainability and food security, both European (Farm to Fork) and French policies are encouraging a profound transition within agri-food systems. Consequently, the transformation of agricultural production methods has become imperative. This article delineates the landscape of transitioning farms across mainland France. It relies on a categorization of farms that integrates their agricultural production methods (organic or conventional) and their product marketing approaches (short circuits or long channels), drawing on data from the 2010 and 2020 agricultural censuses. The analysis yields a detailed map (INSEE canton level) illustrating the evolution of transitional farming from 2010 to 2020, opening the way for discussion on the factors favoring the emergence of certain transition types over others. The outcome reveals a complex geography influenced by sectoral factors such as adaptation to pedo-climatic conditions, agricultural policies, the influence of food chains and distribution channels, historical production system dynamics, and the significance of alternative agricultural networks. Additionally, non-sectoral factors stemming from the socio-residential environment, including proximity to urban centers, tourism, areas experiencing residential migration, and the socio-economic profile of resident populations, as well as local public policies, also play pivotal roles in shaping these transitional landscapes.